Unsettling belongings : settler colonialism in the selected works of Jean Rhys and Elizabeth Bowen - Kuster, Megan E. (Trinity College (Dublin, Ireland). School of English, 2014)
This thesis presents a comparative reading of place in selected works by Jean Rhys and Elizabeth Bowen in the context of settler colonialism. In arguing that Anglo- Irish and Creole identities were formed out of the dynamics of settler colonialism in places where settler states never emerged, the crisis of settler colonialism is understood here to be one of belonging, emanating from a tension between identity and place, encapsulated in the refrain “Who am I, and where do I belong?”
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin